2023
DOI: 10.1155/2023/6643412
|View full text |Cite
|
Sign up to set email alerts
|

Examining Car Accident Prediction Techniques and Road Traffic Congestion: A Comparative Analysis of Road Safety and Prevention of World Challenges in Low-Income and High-Income Countries

Yetay Berhanu,
Esayas Alemayehu,
Dietrich Schröder

Abstract: Road accidents are a significant negative outcome of transportation systems, causing injuries, fatalities, traffic congestion, and economic losses. As cities expand and the number of vehicles on the road increases, traffic accidents (TAs) have become a significant problem. Studies have shown that urban development plays a more significant role in transportation safety than previously thought. Low-income countries have higher fatality rates than high-income countries, according to the Permanent International As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Road safety analysis employs GIS statistical analysis to enhance road safety by pinpointing the location of accident-prone areas. Requires substantial investment in data infrastructure for real-time monitoring [163][164][165] Most of the reviewed papers showed that GIS analysis could be a beneficial tool for the planning phase and for detecting design conflicts. However, fewer efforts have been conducted toward employing GIS techniques during the maintenance phase of transportation infrastructure.…”
Section: Geospatial Analysis Tools For Project Planning (Geospatial A...mentioning
confidence: 99%
“…Road safety analysis employs GIS statistical analysis to enhance road safety by pinpointing the location of accident-prone areas. Requires substantial investment in data infrastructure for real-time monitoring [163][164][165] Most of the reviewed papers showed that GIS analysis could be a beneficial tool for the planning phase and for detecting design conflicts. However, fewer efforts have been conducted toward employing GIS techniques during the maintenance phase of transportation infrastructure.…”
Section: Geospatial Analysis Tools For Project Planning (Geospatial A...mentioning
confidence: 99%
“…Data unavailability in low-and middle-income countries impedes road safety improvements. Access to data is crucial for scientific research on identifying the factors that cause high road risk and assessing the effectiveness of interventions [11].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the need for traffic density prediction has become increasingly urgent [2]. Accurate predictions allow authorities to take timely preventive and responsive actions, optimize traffic flow, and minimize its negative impacts [3]. Therefore, this research emerged as a response to the real-world problems associated with the rapid growth of motorized vehicles [4].…”
Section: Introductionmentioning
confidence: 99%